Thucydides' war narrative : a structural study - Dewald, Carolyn (University of California Press, 2005)
A sustained analysis of the connections between narrative structure & meaning in the 'History of the Peloponnesian War' this volume focuses on the evident change in the underlying principles of the history at the conclusion of the first ten years.